Insight Into Trophic Niche Differentiation in Labeobarbus (Cyprinidae) in the Luhoho Basin (Upper Congo Basin) - Tchalondawa Kisekelwa; Wilondja Alimasi; Mudagi Joyeuse; Musombwa Kubota; Heri Muzungu; Archimède Mushagalusa Mulega; Pieter Lemmens; Emmanuel Vreven; Jos Snoeks; Mulungula Masilya; Steven Bouillon; Benjamin Lejeune (Ecology and Evolution)
ABSTRACT Mouth morphology plays a crucial role in determining the trophic ecology of fish and sometimes underpins important lineage diversification. Freshwater teleost fish species belonging to the genus Labeobarbus, commonly found in Africa, exhibit intra‐ and interspecific variation and differences in the lower jaw occurring within and between species, respectively. Different phenotypes include a curved U‐shape (‘rubberlips’), a straight lower jaw (‘chiselmouth’) and an intermediate morphology known as the smiling phenotype. In some cases, smiling originates from hybridisation between chiselmouth and rubberlips. However, the trophic relationships of different mouth morphologies in the Labeobarbus taxa are still not well understood, particularly in the Congo Basin. Understanding the trophic ecology of Labeobarbus can enhance understanding of adaptive processes in morphologically diverse lineages. This study aims to investigate how differences in mouth morphology among multiple Labeobarbus species in the Luhoho River (Upper Congo Basin) link with different trophic niche uses. We combined information from gut morphometry, gut contents and stable isotope analyses on 202 fish specimens representing six species across four tributaries of the Middle Luhoho. All approaches consistently revealed trophic niche partitioning between chiselmouth and rubberlip species, respectively, more herbivorous/detritivorous and more insectivorous on the omnivory spectrum. In addition, trophic differences were also found between species within each mouth phenotype. Interestingly, the trophic niche of the smiling phenotype differed strongly from those of other phenotypes at all sites except for L. paucisquamatus, for which the trophic niches overlapped in Tchinganda. The pattern of trophic niche of Labeobarbus suggests subtle strategies to partition feeding resources when they occur across a narrow hydrographic scale.